Social media contribution towards ethnocentrism - Ridzuan, Abdul Rauf; Bolong, Jusang; Omar, Siti Zobidah; Osman, Mohd Nizam; Yusof, Rozman; Abdullah, Siti Faidul Maisarah (Elsevier, 2012)
Malaysia is a multiracial country consisting of three main ethnics, namely Malay, Chinese and Indians. National unity among the ethnics is very important to ensure national harmony. Rapid growth and development in a country does not bring anything if people were not united. This can be seen when research done by Jusang Bolong (2008) showed that people like to communicate only with their own ethnic and many Malaysian are indifferent to racial integration which allowing ethnocentrism (Ismail Abdullah, 2009). Social media can be seen as a factor to create solidarity but at the same time encourage ethnocentrism. Therefore, this study is conducted to determine the level of public exposure to social media, the level of ethnocentrism in Malaysia and to identify the relationship between public exposures to social media with ethnocentrism. Researcher will be using survey method in collecting data while Mixed Effect Model will be used as a guide for this research.